Support for the Poor in the Mishnaic Law of Agriculture: Tractate Peah - Brooks, Roger (Book collections on Project MUSE., 2020)
"This study seeks to uncover Tractate Peah's meaning by explaining its laws as they were understood by their authors around 200 C.E. Brooks offers both a new translation of the tractate as well as a commentary and study of it, throwing light on both the individual parts of the Mishnah and the general outlook embedded in the tractate as a whole. The study takes both a diachronic and synchronic approach, allowing us to see how the framers of the Mishnah understood their biblical heritage in light of their own contemporary situation."--Provided by publisher